Investigating the Potential of the Flipped Classroom in Fostering Content Understanding, Promoting Engagement, and Facilitating Differentiated Instruction - BENZERT, Fatima Zohra (My University, 2018)
Academic communities in many parts of the world have embraced various digital innovations as tools to dispel the obstacles that have characterized the traditional way of teaching and learning. One exemplary outgrowth of this gravitation towards technologyenabled instruction, that Algerian higher educational system can exploit, is the flipped classroom. In essence, flipping the classroom is the model wherein the teacher's part of lecturing is moved from the usual institutional environment to a web-based platform where it can be accessed by learners at home. Hence, the better part of class time is allocated to discussion and activities as well as increased student-to-teacher interactions. Our initiatory purpose is to explore whether the model is utilised in the targeted context. Moreover, this study seeks to explore the model’s potential in advancing students’ understanding, elevating engagement and enabling differentiation strategies to be used. In view of the nature of these aims, a mixed-methods mode of investigation has been adopted to collect both qualitative and quantitative data from different perspectives for the present research. It encompasses an observation, an experiment and a students’ questionnaire. The findings reveal that the flipped classroom is not practised in its form as described in the pertinent literature. To a considerable extent, inverting a classroom advances understanding of concepts and encourages learners’ engagement. The results engender an insight into the fact that it is possible to differentiate the instruction within a reversed classroom arrangement.
Case study: First year Master Students of Language and Communication at Abdelhamid Ibn Badis University, Mostaganem
Keywords: Flipped classroom; Understanding; Engagement; Differentiated instruction